Metformin and nitrosamine impurities - P. V., Ajith Kumar; M., Deepa (International Journal of Research in Medical Sciences, 2020)
Metformin is considered as gold standard anti-diabetic drug and is the preferred initial pharmacologic agent for most of the patients with type 2 diabetes mellitus. Metformin is cheap, widely available and safe, backed by pharmaco-epidemiological evidence of more than 60 years regular use in clinical practice. Due to its durable efficacy, once initiated, metformin will be continued as long as it is tolerated and not contraindicated. It has got additional benefits on cholesterol, liver, cardio vascular system and cancer. Recent evidence and recall of metformin extended release formulation due to detection of excess amount of cancer-causing nitrosamine impurities has created concern among health care providers and patients. Adherence to regulatory guidelines and use of approved technologies in manufacturing and quality control may help in solving the issue.